Spin Manipulation in a Metal–Organic Layer through Mechanical Exfoliation for Highly Selective CO2 Photoreduction. (27th March 2023) - Wu, Dayu; Yin, Hua‐Qing; Wang, Zeshi; Zhou, Mingren; Yu, Chengfeng; Wu, Jing; Miao, Huixian; Yamamoto, Takashi; Zhaxi, Wenjiang; Huang, Zetao; Liu, Luying; Huang, Wei; et al.
Abstract: Spin manipulation of transition‐metal catalysts has great potential in mimicking enzyme electronic structures to improve activity and/or selectivity. However, it remains a great challenge to manipulate room‐temperature spin state of catalytic centers. Herein, we report a mechanical exfoliation strategy to in situ induce partial spin crossover from high‐spin ( s =5/2) to low‐spin ( s =1/2) of the ferric center. Due to spin transition of catalytic center, mixed‐spin catalyst exhibits a high CO yield of 19.7 mmol g −1 with selectivity of 91.6 %, much superior to that of high‐spin bulk counterpart (50 % selectivity). Density functional theory calculations reveal that low‐spin 3 d ‐orbital electronic configuration performs a key function in promoting CO2 adsorption and reducing activation barrier. Hence, the spin manipulation highlights a new insight into designing highly efficient biomimetic catalysts via optimizing spin state. Abstract : The manipulation of Fe 3+ spin states from high spin (HS; s =5/2) in bulk crystals to mixed spin lattices (with s =5/2 and low spin (LS); s =1/2) is demonstrated in a two‐dimensional ultrathin metal–organic layer catalyst by mechanical exfoliation. The resulting catalyst has enhanced activity and selectivity for CO2 photoreduction (CO2RR) over the hydrogen evolution reaction (HER).